Hubungan umur dan lama penggunaan IUD dengan efek samping penggunaan IUD - Widyaningtyas, Radicha Nur; Wahyuningsih, Heni Puji; Estiwidani, Dwiana (Jurnal Kesehatan Ibu dan Anak, 2020)
Acceptors IUD inlridonesia tending to decline. Based on data SDKI 2012 recorded 3.9 % PUS use contraceptives IUD. One consideration IUD election is the existence of a side effect. Mejing Wetan having acceptors IUD the largest one in the Ambarketawang Villages a number of 52 people. The purpose of this research is to knew age and the long used of with the side effects of the used IUD at Mejing Wetan 2015. The research is survey analytic by approach cross sectional and use saturated sampling. An instrument of a chief. The subject of study are 52 acceptors IUD. Data analysis using analysis univariatand bivariat and statistict test of chi square with ? 0,05. From this research was obtained the result of p value 0,026 which there are between ages relation with one side effect in the formof pain with contingency coefisient 0,35 and the result ofp value 0.028whichmeans there are relationship beween long the use of to one side effect of the change menstrual with contingency coefisient 0,347. Conclussion research is there is meaningful in statistc between the ages of with side effects iud of pain and there are the relationship between long the use of to change in themenstrual.